Graduates' work experiences in SME's in the northern states of Malaysia - Mohd Shariff, Mohd Noor; Mohd Jani, Mohd Yusop (2008)
This paper was designed to examine university graduates’ expectations and experiences of employment in small and medium enterprises (SMEs) in the Northern States of Malaysia.A self-reported questionnaire data was gathered from 84 graduate employees. Graduates reported positive experiences in many areas.These often exceeded their expectations, and in general over-met expectations were much more common than under-met ones. The graduates’ work appeared to offer quite high autonomy, the chance to develop a wide range of skills, and to progress towards career goals, at least in the short term. In line with previous research, there were signs that pay; within enterprise career prospects and training were relatively weak areas.Taken as a whole, the results substantiated previous research done and challenge more negative images of employment in small enterprises, and also the preoccupation with under-met expectations in the literature on new entrants to enterprises.